1993
DOI: 10.1099/00221287-139-2-203
|View full text |Cite
|
Sign up to set email alerts
|

Sulphonate utilization by enteric bacteria

Abstract: A variety of sulphonates were tested for their ability to serve as nutrients for Escherichia coli, Enterobacter aerogenes and Serratia marcescens. Cysteate, taurine and isethionate could not serve as sole sources of carbon and energy but, under aerobic conditions, could be utilized as sources of sulphur. Both sulphate and sulphonate supported equivalent cell yields, but the generation times varied with the sulphonate being metabolized. The sulphonate-S of HEPES buffer, dodecane sulphonate and methane sulphonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
45
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 12 publications
8
45
0
Order By: Relevance
“…Recognition of the regulation of metabolism of organosulfonates is not new (20)(21)(22), but we now conclude that a global regulatory network is involved (sulfate starvation-induced stimulon, SSIS) (8,23), and this has yet to be evaluated as an ecological phenomenon. The potential ecological relevance of the network should be considered together with the growing awareness of the extent of pollution by sulfonated compounds (e.g.…”
Section: R-ch 2 -Somentioning
confidence: 99%
“…Recognition of the regulation of metabolism of organosulfonates is not new (20)(21)(22), but we now conclude that a global regulatory network is involved (sulfate starvation-induced stimulon, SSIS) (8,23), and this has yet to be evaluated as an ecological phenomenon. The potential ecological relevance of the network should be considered together with the growing awareness of the extent of pollution by sulfonated compounds (e.g.…”
Section: R-ch 2 -Somentioning
confidence: 99%
“…Expression of the tauD gene was shown to depend on functional CysB, and it was fully repressed in the presence of cysteine or cystine and also during growth with sulfate (37). Utilization of sulfate-sulfur in preference to taurine-sulfur (36) is thus due to repression of tauABCD expression in the presence of sulfate.…”
mentioning
confidence: 96%
“…Sulfonate sulfur is of particular interest, as it accounts for over 40% of the total sulfur in the soil (2) and is also released into the environment in the form of man-made pollutants (20). E. coli is able to utilize several aliphatic sulfonates as sulfur sources (36,37). During growth with ethanesulfonate or glutathione, the organism produces a set of proteins which are absent during growth with either cysteine or sulfate (21,30).…”
mentioning
confidence: 99%
“…Sulfonates known to provide sulfur include ethanesulfonate, butanesulfonate, L-cysteate, isethionate (2-hydroxyethanesulfonate), and taurine (2-aminoethanesulfonate) (1,2). None of these sulfonates served as sulfur source under anaerobic conditions, nor could they be utilized as a source of carbon and energy or of carbon, energy, and sulfur under either aerobic or anaerobic conditions (1). The mechanisms of sulfur assimilation from aliphatic sulfonates are unknown, but it has been shown that sulfonate/sulfur enters the assimilatory sulfate reduction pathway at the stage of sulfite (3).…”
mentioning
confidence: 99%